Impact of CFTR Modulators on Longitudinal Cystic Fibrosis Survival and Mortality: Review and Secondary Analysis - Jaime L. Rubin; Craig McKinnon; Gabriel Ghizzi Pedra; Devon A. Morgan; Kimberly Zweig; Theodore G. Liou (Pulmonary Therapy)
Abstract Introduction Cystic fibrosis (CF) transmembrane conductance regulator modulators (CFTRm) have transformed CF care, shifting treatment from only managing symptoms to also addressing the underlying defects that cause CF. CFTRm first entered clinical practice in 2012 and was followed by additional CFTRm combinations—including the approval of elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) in 2019—which treats most CF genotypes. Methods We identified peer-reviewed literature for a narrative review (January 1990 to January 2025) describing longitudinal trends in CF survival and age of death and assessing the influence of CFTRm, particularly ELX/TEZ/IVA. To supplement the existing literature, a secondary analysis of historical, longitudinal trends in the United States CF Foundation Patient Registry (U.S. CFFPR, 1990–2023) was conducted using recent available data. Results Quantitative data from published studies show that the median age of survival and death increased over time but with varying magnitudes across regions. Most cohort and registry-based studies were conducted in settings where CFTRm were not yet widely available, limiting the evaluation of CFTRm effects on survival trends over time. In the secondary U.S. CFFPR analysis, the median survival age increased from 29.0 years in 1990 to 38.6 years in 2012 prior to the introduction of CFTRm and to 68.0 years in 2023, demonstrating substantial improvement following the introduction of CFTRm. Linear regression analyses showed gains in median survival age increased from 0.48 years per year prior to CFTRm to 4.79 years per year after approval of ELX/TEZ/IVA in 2019. Conclusions Study results provide initial evidence of the impact of CFTRm to meaningfully improve survival. Longer-term follow-up data across geographies will provide a deeper understanding of the full impact of CFTRm on predicted CF survival and mortality.